Aesthetics and Artificial Intelligence: Impact and Criticism of Art - Arqoma Nurveda, Mochamad Nursalim, Siti Masitoh (Education Achievement: Journal of Science and Research, 2023)
The background of this research is the technological disruption in the digital era like today in the field of art. This research takes a point of view from the branch of philosophy, namely aesthetics, to examine the impact and criticism that arises. More specifically, explaining how this aesthetic meets artificial intelligence integrated with computers, resulting in art, artists and conventional works of art starting to feel the impact. The aim of this research is to determine the impact and criticism from philosophers or scientists regarding the use of artificial intelligence in the process of creating works of art. This research uses qualitative methods and literature studies from books and journals related to the research theme. The findings from this research are that there are positive and negative impacts from the use of artificial intelligence, from the process to the product of the artwork. While criticism centers on the limited imagination and creativity of artists when using artificial intelligence as a medium for creating works of art.